Estetika : Antara Desain, Teknologi Dan Arsitektur - Tri Prasetyo Utomo (Ornamen, 2008)
Aesthetic experience just is experience of a work’s aesthetic properties and formal relations. But this leads into problems concerning the attribution of aesthetic properties and whether we detect them or they are merely projected. Carroll suggests that the mere fact that we disagree about the attribution of aesthetic properties gives us at least some minimal reason to presume that aesthetic properties are objective. Our response to art is unique and not precisely intellectual, beauty and perfection that we find in works of art do not consist of concepts but sense impressions. Some aesthetic effects available in design, technology and architectural include tonal variation, juxtaposition, repetition, field effects, symmetry/asymmetry, perceived mass, subliminal structure, linear dynamics, tension and repose, pattern, contrast, perspective, 3 dimensionality, movement, rhythm, unity and proportion.key word : aesthetic, design, technology, architecture.